PRESUPPOSITION USED BY THEODORE LAWRENCE IN LITTLE WOMEN MOVIE BY GRETA GERWIG - TASTRID NUR AL-FATH; MUHAMAD JEJEN NURANI (JETA (Journal of English Teaching and Applied Linguistic), 2023)
Movies serve as a reflection of real-life interactions, and the characters’ utterances that convey background knowledge, emotions, and intentions. Therefore, Pragmatics field is often used to study their expressions’ meaning, especially with the theory of Presupposition. Therefore, this study aims to identify and classify the types of presuppositions found in Theodore Lawrence’s utterances by reviewing the related study before handing down to the self-investigation. This study utilizes qualitative analysis of the movie dialogues to understand the intentional meaning of the character's utterances in relation to the conversation context, as well as using SLR method (Systematic Literature Review) of the knowledge from other researchers. This study is also supported by several relevant related studies, by using the existing data from theories, journals, and other educational platforms. After conducting the research analysis, the researcher found that lots of related studies use the theory of George Yule (1996) to define the types of presupposition. In other words, the researcher concludes that to analyze Theodore Lawrence's utterance in the “Little Women” movie, the researcher is reviewing the study from the previous researchers that have been conducted this type of presupposition field analysis